Research Extension Initiatives as Drivers of Women’s Empowerment the Mediating Role of Gender Mainstreaming for Advancing the SDG Agenda 2030 in State Universities and Colleges in Quezon Province - Del Prado, Monica Ivy (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Research extension initiatives are central to the mandate of State Universities and Colleges (SUCs) in the Philippines, yet their contributions to women’s empowerment and the Sustainable Development Goals (SDGs) remain underexamined. Existing literature emphasizes the importance of gender-responsive community programs but provides limited evidence on how gender mainstreaming mediates the link between extension projects and empowerment outcomes. Addressing this gap, this study investigates how SUC-led research extension initiatives drive women’s empowerment in Quezon Province, with gender mainstreaming as a mediating mechanism for advancing the SDG Agenda 2030. This study examines the role of SUC-led research extension initiatives as drivers of women’s empowerment, with gender mainstreaming analyzed as a mediating factor for advancing the SDG Agenda 2030. A mixed-methods design was employed, combining survey responses from 125 women beneficiaries with focus group discussions and key informant interviews involving SUC faculty coordinators, administrators, and community leaders. Findings reveal that extension initiatives significantly enhanced women’s empowerment by improving livelihood opportunities, leadership participation, and decision-making capacity. Importantly, projects that integrated gender-sensitive planning, training, and monitoring reported stronger empowerment outcomes than those where gender concerns were treated as secondary. Challenges included workload imbalances, limited institutional incentives, and fragmented sustainability reporting frameworks, which constrained the visibility of women faculty’s contributions. The study concludes that gender mainstreaming transforms extension initiatives into vehicles for equity and empowerment. By embedding gender-responsive strategies, SUCs can strengthen their dual role in advancing academic innovation and inclusive community development, offering a replicable model for achieving SDG 5 (Gender Equality) and related goals.